Evaluation of postoperative pain on Transversus Abdominis Plane block and Erector Spinae Plane block in patients undergoing gynecological surgery: a prospective, comparative study - D. Tavianto; O. M. Pison; Azka Putra Rakhmatullah (Вестник интенсивной терапии)
INTRODUCTION: Moderate to severe pain after gynecological surgery has an impact on postoperative recovery and mobilization. Transversus Abdominis Plane (TAP) block and Erector Spinae Plane (ESP) block have been used as multimodal analgesia for abdominal surgery. OBJECTIVES: This study aims to compare postoperative pain in patients undergoing either ESP blocks or TAP blocks, and the need for postoperative morphine in patients undergoing gynecological surgery.MATERIALS AND METHODS: This was a single-center, prospective, double-arm, comparative study. Forty subjects were enrolled in this study, and classified into two groups. One group of 20 subjects underwent ESP block, and the remaining 20 subjects underwent TAP block following a gynecologic surgical procedure. Patients were then assessed using with the Numeric Rating Scale (NRS) pain score which will be observed at intervals of 0–1 hour, 1–6 hours, 6–12 hours, and 12–24 hours. Numerical data analysis was done using an unpaired T-test on normally distributed data and the Mann-Whitney test on non-normally distributed data. Categorical data analysis was done using Fisher's Exact Test.